LEADERSHIP DEVELOPMENT CHALLENGES IN - YENDE, FELLENG ANACLETA (My University, 2011)
South Africa can be said to be experiencing rapid changes in the new political dispensation. At the birth of non-racialised democracy in 1994, a number of laws aimed at transforming the government’s administrative structures were formulated. Local government was one such organ of government that was the focus of the new transformative laws. In an effort to implement these new laws and government’s development policies at community level, new structures such as ward councils were established. Ward councillors are the leading representatives of ward councils. Community members elect ward councillors. They represent their respective communities in policy- and decision-making bodies or forums, by articulating their communities’ development needs and policies in line with government’s overall community development mandate and strategies. With the view to addressing the socioeconomic inequalities from the apartheid regime, councillors are strategically positioned to operate as mediators between government and communities. They are mandated to ensure policy implementation so that the communities they lead and represent change for the better if not transform in line with the government’s transformation agenda. This research investigates the leadership development challenges with specific reference to the two wards, namely, Ward 33 and Ward 34 in Soweto. We explore and examine these challenges from the transformational leadership perspective of South Africa’s community development agenda. Our research methodology is qualitative research. We used semi-structured questionnaires were designed and in depth interviews undertaken. The guideline for conducting transformational leadership development challenges or gap analysis was guided by the qualities or competencies of leadership, which include good leadership qualities, function or role, ethics, development challenges. Our research shows that the councillors as leaders have development challenges. Community development needs to have a specific, relevant context. We recommend a leadership development model or a generic leadership development programme in order to enhance leadership qualities of ward councillors. Specifically, we recommend individual leadership development programmes for each councillor
MM - P&DM
Keywords: Service delivery; Leadership